Play Therapy Bagi Anak Korban Child Abuse Psikis - Ritonga, M.Aris Rinaldi; Nihayah, Ulin; Nailussa'adah, Fitriani; Hinayah, Anggita Hikmatul (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2021)
The occurrence of violence against children is due to trivial problems, in this violence mostly occurs in children, even the impact of violence on children is very dangerous, because many children will be depressed, have prolonged trauma, are sensitive, tend to be quiet, rebellious, and more dangerous. Again, children will commit suicide because they are no longer strong with violence. In dealing with these problems, children really need therapy, so that children can return to being like other children, although in realizing it again becomes a child's personality in general it is very difficult. This act of child abuse is very detrimental to the future of the child, because it is clear, the future of the child will be bad, of course the child will not develop well, in the concept of child abuse will use the research method to be carried out namely descriptive research methods, in this study aims to describe every event or incident objectively, from here the violence in child abuse will be well structured, from the results of the analysis a data will be carried out, whose function is so that problems in child abuse research can get the right solution with the help of play therapy for child victims of child abuse abuse . In play therapy, children can get the best direction, even though they can't fully recover like other children, it's just that play therapy can alleviate every problem in child abuse victims.